Epidemiological analysis of lumbar spine degenerative disease diagnosed by MRI: Level-wise and sex-based distribution in the Gandaki province population - Pangeni, Roshan; Dahit, Monu; Mallik, Mukesh; Baral, Santosh; Pradhan, Sulav; Pangeni Lamsal, Laxmi; Chaudhary, Alisha (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Degenerative diseases of lumbar spine is a significant global health concern causing low back pain and is leading contributor of disability and economic burden worldwide. Approximately 266 million people living with low back pain are suffering from lumbar degenerative disease globally and affecting 3.6% of population each year. Because of accurate non-invasive assessment of spinal degenerative diseases, Magnetic Resonance Imaging is considered to be the gold standard tool for imaging spine. This study aimed to determine the frequency of degenerative lumbar spine diseases across different spinal levels and to assess the distribution of degenerative diseases according to sex and age. Methods: A descriptive cross-sectional quantitative study was conducted with 348 participants of age group 28 to 81 years in the Radiology department of Pokhara Academy of Health Sciences in Gandaki province of Nepal. Magnetic Resonance Imaging of the participants were conducted and T1 weighted, T2 weighted, and STIR sequences were done to get sagittal, axial and coronal images of the lumbar spine. Pattern of Lumbar spine degenerative diseases were assessed. Results: The most common site of the diseases was L4/L5 and L5/S1 level. The most common disease diagnosed was disc bulge (91.09%). The degenerative diseases were found in 58.90% of the females compared to 41.1% of the males. The commonest age group to have this disease was 41 to 50 years of age. Conclusions: Women are more susceptible to the disc degenerative diseases causing lower back pain at the lower level of lumbar spine.